2000
DOI: 10.3354/meps199127
|View full text |Cite
|
Sign up to set email alerts
|

Flagging greens:hydrobiid snails as substrata for the development of green algal mats (Enteromorpha spp.) on tidal flats of North Atlantic coasts

Abstract: During the past 3 decades, dense mats of green algae (especially Enteromorpha spp.) have been recorded regularly from tidal flats worldwide. The development of green algal mats on tidal flats may be initiated by overwintering and regrowth of adult plants or by the formation and release of small propagules, i.e. vegetative fragments, zoospores and zygotes. On soft sediments, macroinvertebrates may constitute prime substrata for germination of algal spores. Hydrobud (mud-) snails are widespread along North Atlan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…It has been shown that only coarse sediment is suitable as a substratum for E. prolifera zoospores, and that subsequent germination (Schories 1995) and stable substrata that remain at the illuminated sediment surface are essential for small prop- agules to germinate (Schories et al 2000). It is likely that thalli buried in the sediment are crucial additions to the propagule bank for the impending bloom.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that only coarse sediment is suitable as a substratum for E. prolifera zoospores, and that subsequent germination (Schories 1995) and stable substrata that remain at the illuminated sediment surface are essential for small prop- agules to germinate (Schories et al 2000). It is likely that thalli buried in the sediment are crucial additions to the propagule bank for the impending bloom.…”
Section: Discussionmentioning
confidence: 99%
“…and estuarine environments worldwide (e.g., Fletcher 1996, Schories et al 2000Charlier et al 2007). In addition to having negative effects on tourism, large algal mats can also have deleterious ecological effects, including the uncoupling of biogeochemical cycles in sediments from those in water column (Valiela et al 1997), a negative impact on seagrass beds due to shading, disruption of feeding by wading birds (Raffaelli et al 1998), development of a lethal environment due to oxygen deficiency (Charlier et al 2007), and a shift from a high-diversity mixture to low-diversity assemblages of fast-growing annuals (Worm et al 2001).…”
mentioning
confidence: 99%
“…Hydrobia spp. ; Schories et al 2000). In late summer, up to 50% of the shallow embayments are covered by algal mats that float at the water surface (Pihl et al 1999).…”
Section: Experimental Designmentioning
confidence: 99%
“…vary strongly with season and locations, e.g. from 440 ± 260 individuals m -2 in June 1996 to 35,520-14,544 individuals m -2 in August 1996 (Schories et al, 2000). Herbivore densities were established based on a combination of the size of the animals relative to the size of the experimental unit, their natural densities per surface area and the amount of seaweed biomass that could be placed in each unit.…”
Section: Grazersmentioning
confidence: 99%